2017
DOI: 10.1371/journal.pone.0172540
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence during pregnancy and its association with preterm birth and low birth weight in Tanzania: A prospective cohort study

Abstract: IntroductionIntimate partner violence (IPV) is a public health problem that affects millions of women worldwide. The role of violence as an underlying factor in poor birth outcomes remains an area where strong evidence is lacking. The aim of this study was to determine the association between intimate partner violence (IPV) and preterm delivery (PTB) and low birth weight (LBW).Materials and methodsA prospective cohort study was conducted among 1112 pregnant women attending antenatal care in Moshi–Tanzania. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
97
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 29 publications
23
97
7
2
Order By: Relevance
“…This finding is in line with existing evidence in the literature that women are more likely to disclose violence to a healthcare provider. 45 A study evaluating the similar intervention through a randomised control trial also showed improvement in the health status of women 22 but another study in Peru found no statistically significant impact on health-related quality of life. 40, 41 The effect of violence on physical and mental health of women found in the study has been well documented in other literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with existing evidence in the literature that women are more likely to disclose violence to a healthcare provider. 45 A study evaluating the similar intervention through a randomised control trial also showed improvement in the health status of women 22 but another study in Peru found no statistically significant impact on health-related quality of life. 40, 41 The effect of violence on physical and mental health of women found in the study has been well documented in other literature.…”
Section: Discussionmentioning
confidence: 99%
“…A study in an ANC setting has also found the crucial role of social support in mitigating the consequences of IPVDP. 45 A study evaluating the similar intervention through a randomised control trial also showed improvement in the health status of women 22 but another study in Peru found no statistically significant impact on health-related quality of life. 23 This study suggests that the number of counselling sessions required to have an impact can vary from woman to woman.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of IPV on PTB were examined by three studies. Of three, two studies found positive association between IPV and PTB [35,53] and one found no association [58]. Women exposed to IPV (AOR 2.5; 95% CI: 2.19-2.96) and physical violence (AOR 5.3; 95% CI: 3.95-7.09) during pregnancy were more likely to experience PTB [53].…”
Section: Sensitivity Analysesmentioning
confidence: 93%
“…The studies were included from 11 East African countries. Nineteen studies were from Tanzania [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regardless of these evidence, IPV continues to be a serious challenge for the promotion of women's health especially in the sub-Saharan African countries. Given women's predominant role in childcare, the effects of IPV can extend well beyond women's own health and are associated with poor anthropometric and neurodevelopmental issues among infants and toddlers [3,5,21]. Based on these well-documented findings, it is assumable that IPV is also contributing to the high maternal and child mortality rates, which can hinder the progress to several Sustainable Development Goals relevant to women's health (SDG 3), gender-equality (SDG 5) and peace and justice (SDG 10).…”
Section: Introductionmentioning
confidence: 99%